2013
DOI: 10.1371/journal.pone.0059108
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural White Matter Changes in the Corpus Callosum of Young People with Bipolar Disorder: A Diffusion Tensor Imaging Study

Abstract: To date, most studies of white matter changes in Bipolar Disorder (BD) have been conducted in older subjects and with well-established disorders. Studies of young people who are closer to their illness onset may help to identify core neurobiological characteristics and separate these from consequences of repeated illness episodes or prolonged treatment. Diffusion tensor imaging (DTI) was used to examine white matter microstructural changes in 58 young patients with BD (mean age 23 years; range 16–30 years) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 51 publications
8
42
1
Order By: Relevance
“…The corpus callosum and thalamic radiation of middle-aged and drug-naïve BD populations showed abnormal axial (AD) and radial diffusivity (RD) values [21-23]. Increased RD values have been observed in the cingulum, the superior and inferior uncinated fasciculus, the corpus callosum and the internal capsule of BD I patients when compared to their unaffected relatives and healthy controls [24].…”
Section: Introductionmentioning
confidence: 99%
“…The corpus callosum and thalamic radiation of middle-aged and drug-naïve BD populations showed abnormal axial (AD) and radial diffusivity (RD) values [21-23]. Increased RD values have been observed in the cingulum, the superior and inferior uncinated fasciculus, the corpus callosum and the internal capsule of BD I patients when compared to their unaffected relatives and healthy controls [24].…”
Section: Introductionmentioning
confidence: 99%
“…In other neurodegenerative diseases, white matter disease (WMD) is associated with cognitive impairment [Prins et al, 2005; Gouw et al, 2006], physical decline [Zheng et al, 2012] and depressive symptoms in the elderly [de Groot et al, 2000]. Furthermore, WMD occurs in schizophrenia [Voineskos et al, 2013] and bipolar disorder [Ahn et al, 2004; Lagopoulos et al, 2013], and is correlated with mortality in patients with and without dementia or stroke [Bokura et al, 2006; Kerber et al, 2006; Kuller et al, 2007; Ikram et al, 2009; Oksala et al, 2009]. …”
Section: Introductionmentioning
confidence: 99%
“…Reduced signal intensity in youth with BD has been identified in all callosal subregions , a finding that has been replicated in adults with BD . Finally, a diffusion tensor imaging study revealed decreased structural integrity across the length of the corpus callosum in youth with BD ; the authors speculated that this may negatively influence attention and executive functioning. Nevertheless, the contribution of corpus callosum abnormalities in youth with BD remains unclear.…”
mentioning
confidence: 99%